Learning Achievements among Nursing Students through Active Learning - วุฒิวงศ์ เกศินี; เหมะวิบูลย์ ดารินทร์; แม้นมาลัย สุกาญจนา (Journal of Nurses Association of Thailand Northern Office, 2019)
The purpose of the quasi-experimental one group only post-test design was learning achievements while learning through the active learning of the nursing students in McCormick of Nursing, Payap University. The sample was to evaluate 98 nursing students who registered in GE 142 Health Myths in the first semester of the 2017 academic year. The sample was obtained by using the formula of Taro Yamane at the confidence level 95% and was selected by stratified random sampling and then using simple random sampling without replacement. The instruments employed in the research comprised of 2 parts: 1) experimental instrument was the lesson plan of active learning activity, and 2) the data-collecting instruments consisting of an evaluation forms, an achievement tests, and the students’ reflection regarding learning. The data were analyzed using frequency, percentage, mean, standard deviation and t-test. The research results revealed that after receiving the active learning method, the students’ achievement was statistically significantly higher than criteria at p< .05. Active learning method is recommended in providing knowledge to nursing students to increase their learning achievement in the next academic year.